Direitos humanos e transexualidade: a educação como luta contra a (psico)patologização - Barbosa, Rafaelly Rocha Lima (2019)
From the very beginning of his life, the human being is constituted based on a reality that advocates biological sex as a determinant of the gender roles it must assume, thus characterizing a binary society. However, there are bodies, subjects, that break with these heteronormative and patriarchal ideals, which subvert them, these are the transgender. To research about them is initially to know that from a social construct they are placed as worthless lives, as abjects. And it is precisely because they are in this position that they are likely to suffer the most varied forms of violence, such as: psychopathologization of their gender identity; family abandonment; difficulty in entering the labor market; transphobia; among others. Thus, the present work seeks to analyze, historically, from a documentary research - based on the theory of Human Rights, and on laws, ordinances, norms and resolutions of government agencies and federal councils of psychology and medicine - as occurred positivization of the rights of transgender people. However, it also proposes to understand this documentary process from a critical view, based on the Critical Theory of Law, questioning that the positivization of rights does not guarantee rights, that is, there is a long way to effectively ensure what is preached in the legislations. Finally, is dedicated to the theme of Human Rights Education as a possibility of overcoming the oppressive and unequal Brazilian reality.